Pendampingan Belajar Membaca Melalui Metode Suku Kata dalam Meningatkan Keterampian Membaca di Bimbel Baskara Sidoharjo Pulung Ponorogo - Refi Ariani; Medina Nur Asyifa Purnama (Social Science Academic, 2025)
The purpose of this study was to determine the effectiveness of the syllable method and to explain how to use the syllable method to improve students' reading skills in Pulung Village, especially in Krajan, Sidoharjo Village, Pulung District, Ponorogo Regency. In this mentoring-based research, the authors used the ABCD (Asset Based Community Development) approach. According to Munawar Ahmad, Asset Based Communities Development (ABCD) is an approach model in community development, besides this research uses an advocacy approach (assistance) with the type of case study research based on data collected from research results. The data is used to describe the implementation of learning to read using the syllable method. It aims to see the effectiveness, advantages, and disadvantages of applying the syllable method.The results of the study can be concluded that the syllable method can improve the reading ability of children in the hamlet. Krajan, Sidoharjo Village, Pulung District, Ponorogo Regency. This can be seen from the increase in students' reading skills.